Pesticide exposure and lung function: a systematic review and meta-analysis. (21st December 2019) - Ratanachina, J; De Matteis, S; Cullinan, P; Burney, P
Abstract: Background: Epidemiological studies have reported associations between pesticide exposure and respiratory health effects, but the quantitative impact on lung function is unclear. To fill this gap, we undertook a systematic review of the available literature on the association between pesticide exposure and pulmonary function. Aims: To examine all available literature regarding the relationship between occupational and environmental exposure to pesticides and lung function. Methods: We searched MEDLINE, EMBASE and Web of Science databases to 1 October 2017 without any date or language restrictions using a combination of MeSH terms and free text for 'pesticide exposure' and 'lung function'. We included studies that met the criteria of our research protocol registered in PROSPERO, and we assessed their quality using a modified Newcastle-Ottawa scale. Results: Of 2356 articles retrieved, 56 articles were included in the systematic review and pooled in meta-analyses for forced expiratory volume in 1 s (FEV1 )/forced vital capacity (FVC), FVC and FEV1 . There was tentative evidence that exposure to cholinesterase (ChE) inhibiting pesticides reduced FEV1 /FVC and no evidence that paraquat exposure affected lung function in farmers. Conclusions: Respiratory surveillance should be enhanced in those exposed to ChE-inhibiting pesticides which reduced FEV1 /FVC according to the meta-analysis. Our study is limited by heterogeneity between studies due to different types of exposure assessment to pesticides and potential confounders. Further studies with a more accurate exposure assessment are suggested.